Analysis code for publication: 'The aperiodic exponent of subthalamic field potentials reflects excitation/inhibition balance in Parkinsonism' - Wiest, C; Tan, H (University of Oxford, 2022)
The analysis code is written for MATLAB, and version 2020b was used for the associated publication.